Framework for assessing and mitigating the impacts of offshore wind energy development on marine birds. (December 2022) - Croll, Donald A.; Ellis, Aspen A.; Adams, Josh; Cook, Aonghais S.C.P.; Garthe, Stefan; Goodale, Morgan Wing; Hall, C. Scott; Hazen, Elliott; Keitt, Bradford S.; Kelsey, Emma C.; Leirness, Jeffery B.; Lyons, Don E.; et al.
Abstract: Offshore wind energy development (OWED) is rapidly expanding globally and has the potential to contribute significantly to renewable energy portfolios. However, development of infrastructure in the marine environment presents risks to wildlife. Marine birds in particular have life history traits that amplify population impacts from displacement and collision with offshore wind infrastructure. Here, we present a broadly applicable framework to assess and mitigate the impacts of OWED on marine birds. We outline existing techniques to quantify impact via monitoring and modeling (e.g., collision risk models, population viability analysis), and present a robust mitigation framework to avoid, minimize, or compensate for OWED impacts. Our framework addresses impacts within the context of multiple stressors across multiple wind energy developments. We also present technological and methodological approaches that can improve impact estimation and mitigation. We highlight compensatory mitigation as a tool that can be incorporated into regulatory frameworks to mitigate impacts that cannot be avoided or minimized via siting decisions or alterations to OWED infrastructure or operation. Our framework is intended as a globally-relevant approach for assessing and mitigating OWED impacts on marine birds that may be adapted to existing regulatory frameworks in regions with existing or planned OWED. Highlights: We outline a unified approach to address offshore wind farm impacts to marine birds. Empirical measurement of impact in the marine environment presents challenges. Modeling approaches are key to estimate impacts and direct mitigation efforts. Net positive impacts of offshore wind may be achieved via compensatory mitigation. Impacts estimation and mitigation may be most effective on a regional scale.